Small Extracellular Vesicles in the Development, Diagnosis, and Possible Therapeutic Application of Esophageal Squamous Cell Carcinoma - Zhao, Zheng; Yang, Shuyue; Zhou, Anni; Li, Xiao; Fang, Rui; Zhang, Shutian; Zhao, Guiping; Li, Peng (Frontiers in Oncology, 2021)
Esophageal Squamous Cell Carcinoma (ESCC) persists among the most lethal and broad-spreading malignancies in China. The exosome is a kind of extracellular vesicle (EV) from about 30 to 200 nm in diameter, contributing to the transfer of specific functional molecules, such as metabolites, proteins, lipids, and nucleic acids. The paramount role of exosomes in the formation and development of ESCC, which relies on promoting intercellular communication in the tumor microenvironment (TME), is manifested with immense amounts. Tumor-derived exosomes (TDEs) participate in most hallmarks of ESCC, including tumorigenesis, invasion, angiogenesis, immunologic escape, metastasis, radioresistance, and chemoresistance. Published reports have delineated that exosome-encapsulated cargos like miRNAs may have utility in the diagnosis, as prognostic biomarkers, and in the treatment of ESCC. This review summarizes the function of exosomes in the neoplasia, progression, and metastasis of ESCC, which improves our understanding of the etiology and pathogenesis of ESCC, and presents a promising target for early diagnostic in ESCC. However, recent studies of exosomes in the treatment of ESCC are sparse. Thus, we introduce the advances in exosome-based methods and indicate the possible applications for ESCC therapy in the future.